갯벌 미생물 다양성 모니터링 시료 채취 개수 및 간격 선정을 위한 지구통계학적 기법과 데이터 마이닝 적용 연구 - 양지훈(Ji Hoon Yang); 이재진(Jae Jin Lee); 유근제(Keun Je Yoo); 박준홍(Joon Hong Park) (Daehan hwan'gyeong gonghag hoeji, 2010)
Tidal mudflat is a reservoir for diverse microbial resources. Microbial diversity in tidal mudflat sediment can be easily influenced by various human activities. It is necessary to take representative samples to monitor microbial diversity in tidal mudflat sediments. In this study, we analyzed the microbial diversity and chemical characteristics of vegetation and non-vegetation tidal mudflat regions in the Kangwha tidal mudflat using geo-statistics and data-mining. According to the geo-statistical analysis, most correlation range values for the vegetation region were smaller than those for the non-vegetation region, which suggested that the shorter number and interval of sampling are required for the vegetation tidal mudflat environment due to its higher degree of chemical and biological complexity and heterogeneity. The data-mining analysis suggested that the organic content and nitrate were the major environmental factors influencing microbial diversity in the vegetation region while pH and sulfate were the major influencing factors in the non-vegetation region. Using the geo-statistical and data-mining integration approach, we proposed a guideline for determining the sampling interval and number to monitor microbial diversity in tidal mudflat. 갯벌 퇴적토는 미생물 다양성이 매우 높다고 알려져 있다. 하지만 인위적인 교란에 의해 갯벌 퇴적토 내 미생물 다양성이 달라질 수 있다. 지속적인 퇴적토 내 미생물 다양성 모니터링을 위해서는 대표성을 지닌 시료의 채취가 중요하다. 본 연구에서는 강화도 여차리 갯벌을 대상으로 식생이 있는 지역과 식생이 없는 지역의 미생물 다양성과 이화학적 특성치를 지구 통계학적으로 비교분석 하였다. 갯벌 시료에서 측정된 미생물 다양성과 다양한 이화학적 특성치를 지구통계학적으로 분석한 결과, 식생이 존재하는 지역에서의 상관거리가 식생이 존재하지 않는 지역에 비하여 대체로 짧다는 것을 알 수 있었다. 이는 식생이 존재하는 지역의 높은 생태학적 및 이화학적 복잡성과 이질성으로 인해 식생이 존재하는 지역에서는 식생이 존재하지 않는 지역에서 보다 비교적 좁은 간격으로 시료를 채취해야 한다는 것을 의미한다. 데이터 마이닝 기법을 사용하여 미생물 다양성에 영향을 주는 주요 환경영향 인자를 분석한 결과, 식생이 존재하는 지역에서는 유기물 함량과 질산염이온, 식생이 존재하지 않는 지역에서는 pH와 황산염이온이 미생물 다양성에 영향을 끼친다는 것을 알 수 있었다. 이러한 지구통계학 및 데이터 마이닝 분석 결과들을 활용해서 갯벌 퇴적토 내 미생물 다양성 측정을 위한 시료 채취 간격 및 개수 선정 지침을 본 연구에서 제안하였다.